Major Bleeding Risk in Patients With Non-valvular Atrial Fibrillation Concurrently Taking Direct Oral Anticoagulants and Antidepressants - Chang, Kuo-Hsuan; Chen, Chiung-Mei; Wang, Chun-Li; Tu, Hui-Tzu; Huang, Yu-Tung; Wu, Hsiu-Chuan; Chang, Chien-Hung; Chang, Shang-Hung (Frontiers in Aging Neuroscience, 2022)
Direct oral anticoagulants (DOACs) are commonly prescribed with antidepressants that may increase bleeding risk. Here we assessed the association between DOACs with and without concurrent antidepressants and major bleeding risk in patients with atrial fibrillation (AF) by a retrospective cohort study included patients with AF who received prescriptions of DOACs in Taiwan’s National Health Insurance database between 2012 and 2017. Adjusted rate ratio (ARR) of major bleeding was calculated by comparing incidence rate adjusted with Poisson regression and inverse probability of treatment weighting using the propensity score between patient-times with and without antidepressants. Among 98863 patients with AF, concurrent use of bupropion with DOACs increased the risks of all major bleeding (ARR: 1.49, 95% CI: 1.02-2.16) and gastrointestinal hemorrhage (ARR: 1.57, 95% CI: 1.04-2.33). An increased risk of intracerebral hemorrhage (ICH) was associated with the combinations of DOACs with selective serotonin reuptake inhibitors (SSRIs, ARR: 1.38, 95% CI: 1.08-1.76), particularly in paroxetine (ARR: 2.11, 95% CI: 1.17-3.81), and tetracyclic antidepressants (TeCAs, ARR: 1.34, 95% CI: 1.01-1.78). In subgroup analyses stratified by individual NOACs, SSRIs increased the risk of ICH in the dabigatran-treated patients (ARR: 1.55, 95% CI: 1.04-2.33). The combinations of apixaban and serotonin-norepinephrine reuptake inhibitors were associated with a higher risk of all major bleeding (ARR: 1.63, 95% CI: 1.04-2.55). These results clearly indicate the drug–drug interactions between DOACs and antidepressants, which should be carefully considered when prescribing DOACs in adult patients.